STUDY RELATED TO THE EVOLUTION OF TABLE TENNIS IN OLYMPIC GAMES FROM THE PERSPECTIVE OF SPORT HISTORY AND GEOGRAPHY - Ștefan MAROTI; Paula APOSTU; Șerban DOBOȘI; Vasile GRAMA (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
Our intention is to study the evolution of Olympic tournaments of table tennis, both from the perspective of the history of Olympic Games and geography. In the introductory part, the authors attempt to place this article into the present works written on this subject, addressing several research essays related to sport and particularly to the Olympic sport as a result of joint study made by specialists in sport and geography. Then, we describe the main events that led to the inclusion of table tennis in the Olympic Games competitions. The evolution in time of table tennis Olympic tournament, the athlete’s attendance and medals obtained by them are described and analyzed by linking maps to tables and by using various graph representations.